Current Trends in Steroid Dose Choice and Frequency of Administration of Epidural Steroid Injections: A Survey Study. Issue 1 (11th September 2019) - Vydra, Darrell; McCormick, Zack; Clements, Nate; Nagpal, Ameet; Julia, Jonathan; Cushman, Daniel
Abstract : Background: Epidural steroid injections (ESI) are commonly used to treat refractory radicular spinal pain. Although evidence suggests that an increasing cumulative dose of exogenous corticosteroid may be harmful, knowledge of current practice patterns is limited regarding the choice of dose and frequency of epidural steroid injections (ESIs). Objective: Describe current practice trends in the dose selection and frequency of administration of transforaminal ESIs (TFESIs) and interlaminar ESIs (ILESIs). Design: Cross‐sectional survey study. Setting: Not applicable. Participants: Three hundred fourteen physician members of the Spine Intervention Society (SIS). From May to June 2018, an online survey was distributed to 5907 physician members of the SIS. Interventions: Not applicable. Main Outcome Measures: Corticosteroid dose used by practitioners and the number of annual ESIs administered per patient. Results: Three hundred fourteen physicians responded to the survey. For single cervical or lumbar injections of dexamethasone, most physicians (56.0%) reported using 10 mg; 17% of physicians reported use of doses greater than 10 mg, with 6% using a dose of 20 mg per injection level. The most common particulate corticosteroid dose used during both cervical and lumbar ILESIs was 80 mg (cervical = 55.4%, lumbar = 54.7%). During cervical and lumbar ILESIs, 17% and 12.7% of physicians reported using doses greater than 80 mg, respectively. Almost 10% of physicians reported performing cervical TFESIs with particulate steroids. Forty percent of physicians reported allowing four ESIs at a given spinal segmental level per year (cervical/thoracic/lumbosacral). A small percentage of physicians reported allowing more than six ESIs annually (6%) and >10 injections annually (1%). Conclusions: There is considerable variability among this large cohort of interventionists with regard to corticosteroid dose selection and epidural steroid injection frequency. A small proportion of respondents reported Mulitsociety Pain Workgroup guideline‐discordant use of particulate steroids during cervical TFESIs. These findings demonstrate a need for additional research regarding both the reasons for such variation in care and the reasons for guideline‐discordant practice in a subset of physicians. Level of Evidence: IV.